2008
DOI: 10.1103/physrevlett.101.043001
|View full text |Cite
|
Sign up to set email alerts
|

Intrashell Electron-Interaction-Mediated Photoformation of Hollow Atoms near Threshold

Abstract: Double photoionization (DPI) of an atom by a single photon is a direct consequence of electron-electron interactions within the atom. We have measured the evolution of the K-shell DPI from threshold up in transition metals by high-resolution x-ray emission spectroscopy of the Kh alpha hypersatellites, photoexcited by monochromatized synchrotron radiation. The measured evolution of the single-to-double photoionization cross-section ratio with excitation energy was found to be universal. Theoretical fits suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
25
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 31 publications
9
25
1
Order By: Relevance
“…At high excess energies KO becomes negligible and the P KK ratios approach the SO photoabsorption asymptotic limit. These results are in accord with the conclusions of Kanter et al [12] and Huotari et al [13] for the prevalence of KO in the nearthreshold region and for intermediate photon energies of the P KK photon energy evolution. The very good agreement between the experimental data for the photon energy dependence of P KK and the SO-KO model fit supports this physical picture for the K-shell double photoionization for low-Z neutral atoms.…”
Section: Tablesupporting
confidence: 83%
See 3 more Smart Citations
“…At high excess energies KO becomes negligible and the P KK ratios approach the SO photoabsorption asymptotic limit. These results are in accord with the conclusions of Kanter et al [12] and Huotari et al [13] for the prevalence of KO in the nearthreshold region and for intermediate photon energies of the P KK photon energy evolution. The very good agreement between the experimental data for the photon energy dependence of P KK and the SO-KO model fit supports this physical picture for the K-shell double photoionization for low-Z neutral atoms.…”
Section: Tablesupporting
confidence: 83%
“…Double-to-single K-shell photoionization ratios PKK for Al, Ca, and V versus the photon beam energy. For Ca and V the present experimental data are compared to those of Oura et al [38] and Huotari et al [13]. The solid black lines correspond to the best fits to our data with the SO-KO empirical model.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It was found that a time-dependent perturbation theory [3] describes well the double photoionization of outer-shell electrons in low-Z atoms; for inner shells and higher Z atoms significant deviations were found [4,5], indicating that other mechanisms besides the shakeoff are at work. In the latest work a semiclassical knockout effect was suggested to dominate the near-threshold double 1s photoionization in 3d transition metals [6].One of the most interesting multielectron features is double excitations exhibiting discrete resonances in the preedge region. These processes are extremely weak when both electrons are excited from core levels, but they become more probable if a valence electron takes part in the excitation.…”
mentioning
confidence: 99%